Comparison of the sensory properties of UHT milk from different countries - Oupadissakoon, Gaewalin; Chambers, Delores H.; Chambers, Edgar, IV (My University, 2009)
Shelf-stable milk, also known as ultra-high temperature (UHT) milk is the most common form of milk in many parts of the world. This study compared the differences in flavor and texture of 37 commercially available UHT and sterilized milk samples including whole, 2% reduced-fat, and low-fat milk obtained from markets in seven countries: France (n = 2), Italy (n = 11), Japan (n = 1), Korea (n = 2), Peru (n = 3), Thailand (n = 13), and the U.S. (n = 5). Five highly trained panelists used flavor and texture profiling to describe the sensory properties of each milk sample. Data were analyzed by principal component analysis and hierarchical cluster analysis. Higher levels of processed, chalky, brown, and cooked flavor notes generally corresponded to lower levels of fresh dairy flavor characteristics. In general, samples did not vary consistently within a country. Fat content did not correlate with dairy fat flavor or with viscosity. This research suggests that companies’ manufacturing processes for UHT milk may have more impact than country or fat content in determining sensory properties of UHT milk.
Keywords: UHT milk; Sensory properties; Flavor; Texture; Milk; Comparison